Immersive Visualization Interface for Endoscopy Analytics and Debriefing - Monticelli, Jonas; Wagner, Jorge; Maciel, Anderson; Torchelsen, Rafael P.; Freitas, Carla; Nedel, Luciana (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
Endoscopic surgery is a complex procedure and is challenging for students to learn without risking the patient. Meanwhile, simulators have been developed to provide a safe environment for students to practice and learn, guaranteeing the patient’s safety. During a surgery simulation, many data are produced, including the patient’s vital signs and the indicators of the user’s performance, i.e., the endoscope operation. Combining both data in a timeline provides a picture of the patient’s condition. This work proposes a new perspective for immersive visualization of an endoscopic surgery simulation by integrating a virtual reality simulator with a series of panels for presenting data collected during the simulation. Additionally, after the surgery training, one may graphically analyze and reason the simulation session in a timeline without leaving the immersive environment. This practice, so-called debriefing, is usual in any medical practice. The proposed interface can potentially enhance the comprehension of a patient’s state during surgical procedures. Medical practitioners and surgeons can also use it to evaluate medical students’ proficiency, leading to possible changes in surgical training and providing new tools and resources for medical education.